Fluorescence enhancement of N2O2-type dipyrrin ligand in two step responding to zinc(II) ion - Song, Hyesun; Rajendiran, Senkuttuvan; Koo, Eunhae; Min, Byoung Koun; Jeong, Soon Kwan; Thangadurai, T. Daniel; Yoon, Sungho (ELSEVIER SCIENCE BV, 2012)
Fluorescence imaging is well-suited for the live imaging of biological Zn(II), which has no facile spectroscopic or magnetic signature. The successful application of this methodology requires the development of robust Zn(II) imaging agents that display high sensitivity, selectivity and temporal fidelity. In this study. a N2O2-type dipyrrin based bimolecular zinc(II) complex was produced and shown to have sharper, blue-shifted and more enhanced fluorescence emission. An approximate threefold fluorescence enhancement was achieved within the micromolar concentration range, which is an important parameter for Zn(II) detection in vivo. The increase in emission intensity was due to the dominant role of aryl-ring rotation in governing the excited state dynamics and fluorescence properties of the dipyrrin dye. Fluorescence titration showed that the ligand complex exhibited very strong zinc(II) binding affinity when compared to that in the binuclear chloro complex. The fluorescence emission changes in the dipyrrin dye to zinc(II) ion could be observed not only using instruments but also by the naked-eye (violet -> sky blue). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 2-PHOTON MICROSCOPY; ENERGY-TRANSFER; METAL-IONS; COMPLEXES; STATE; RHODIUM(I); DYNAMICS; SENSORS; DYES